2017
DOI: 10.3126/jcmsn.v12i4.15593
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Congenital Heart Diseases in Eastern Nepal: A tertiary care hospital experience

Abstract: Background & Objectives: Congenital heart diseases are neglected especially in world’s poorest nations and appear to be ignored and unexplored dimension of health. The exact prevalence and spectrum of congenital heart diseases in Nepal is largely unknown. The aim of this study was to describe the local experience on the magnitude and the pattern of congenital heart disease in order to increase the awareness of the public and health policy makers on its burden in Nepal.Materials & Methods: This is an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
4
1
2
Order By: Relevance
“…There were no cases of TOF as it is a well-known fact. These findings were similar to the findings of the other studies by Vashishta VM et al (18) & L Shamima et al (15) .…”
Section: Present Study2016 112supporting
confidence: 83%
See 1 more Smart Citation
“…There were no cases of TOF as it is a well-known fact. These findings were similar to the findings of the other studies by Vashishta VM et al (18) & L Shamima et al (15) .…”
Section: Present Study2016 112supporting
confidence: 83%
“…(23) 108 Sonali Tank et al,2004 (25) 147 Mohammed S et al,2006 (14) 89 Memon Y et al 2007 (26) 80 Borzouee M et al,2008 (17) 1380 Shah et al, 2008 (18) 84 Rajendra Kumar Jatav et al, 2014 (21) …”
Section: Discussionmentioning
confidence: 99%
“…4,5 The prevalence of congenital heart disease was found to be 5.8/1000 hospitalized patients by Shah GS et al, 13.28% by Sawant SP et al conducted at Mumbai whereas in the present study it was 6.49%. 5,6 Acyanotic heart disease constituted 27.50% of the congenital heart disease according to Abquari S. 4 In the present study the prevalence was found to be 13.69%. A study by Shah GS estimated the prevalence of cyanotic congenital heart disease to be 31%.…”
Section: Discussioncontrasting
confidence: 50%
“…A study by Shah GS estimated the prevalence of cyanotic congenital heart disease to be 31%. 5 The increased prevalence of acyanotic heart disease may possibly be due to the increased prevalence of gestational diabetes mellitus in the state of Tamil Nadu. The prevalence of cleft lip and palate was found to be 11% to 15.3% by Pavri S et al, conducted at Canada, whereas in the present study it was 9.6%.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Baspinor Q et al, 18 male/ female was 1:1. Shah GS et al 19 found male to female ratio1.5:1. In our study most of the CHD were detected in infancy (76.7%) and 7.8% of beyond five years.…”
Section: Discussionmentioning
confidence: 99%